Regional Commercial Center - Baustita, Meinard C. (Manila : National University, 2003)
A commercial center is a complex of retail stores and related facilities planned as a unified group to give maximum shopping convenience to the customer and maximum exposure to the merchandise.
Title page -- Letter of endorsement -- Jury's Approval sheet -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of references -- Chapter IV. Design framework -- Chapter V. Design Analysis and presentation -- Chapter VI. Conclusion and recommendation.
Includes bibliographical references.
Keywords: COMMERCIAL COMPLEX -- PLANNING